2017
DOI: 10.1108/rsr-07-2016-0043
|View full text |Cite
|
Sign up to set email alerts
|

Mining writing center data for information literacy practices

Abstract: • Purpose ○ Collaborations between writing centers and libraries create opportunities for providing information literacy intervention for students doing researched writing. This case study gathered data from writing center logs to uncover if and how information literacy activity was occurring during consultations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Tutors also engaged students in conversations about selecting, evaluating, and documenting sources. Similarly, Graves, Anders, and Balester (2017) found new opportunities for collaboration between writing centres and libraries by examining tutoring logs for indications that tutors had provided information literacy instruction.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Tutors also engaged students in conversations about selecting, evaluating, and documenting sources. Similarly, Graves, Anders, and Balester (2017) found new opportunities for collaboration between writing centres and libraries by examining tutoring logs for indications that tutors had provided information literacy instruction.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…However, in practice, this relationship is scarce. According to Graves et al . (2017), who studied the interaction between Texas A&M University’s writing centers and libraries by analyzing records of students’ consults, found that only 13 per cent of operations could be considered to relate to information literacy and in only one per cent of cases the writing center staff considered it convenient to refer the student to a librarian.…”
Section: Theoretical Framework (Literature Review)mentioning
confidence: 99%
“…David James Brier explored drawing as an instructional method to teach information literacy [3]. Stephanie J. Graves explored collaborations between writing centers and libraries which create opportunities for providing information literacy intervention for students doing researched writing [4]. Kuan-nien Chen explored the essential features of information literacy; what role it should play in university library user education; and how programs can be best implemented [5].…”
Section: Introductionmentioning
confidence: 99%